State Defence Education Curriculum (Study at Taruna Nusantara High School) - Kurniawan, Dedi Muhammad; Raharjo, Tri Joko; Kustiono, Kustiono (Universitas Negeri Semarang, 2018)
State Defense is a constitutional mandate that must be carried out by Indonesian citizens; Taruna Nusantara High School is one of the schools that apply the State defense Education curriculum contained in the special curriculum. This study aims to analyze the development of the State defense Education curriculum at Taruna Nusantara High School. This type of research is qualitative by using a case study approach for in-depth analysis. Data collection techniques using observation, interviews, and documentation studies. Data analysis techniques applied in this study were data reduction, data presentation, and draw conclusions. The issues discussed include the concept, design, and implementation of State Defense Education. The results showed that the concept of developing the National Martial Arts curriculum at Taruna Nusantara High School by using forms of subject curriculum, activities and integrated curriculum while the design of the development of the National Martial Arts curriculum was needs-oriented, formulated curriculum development goals, organized curriculum contents, implemented and evaluated curriculum. The implementation of the National Defence Education curriculum is conducted by developing patterns of teaching, caring, and training. The results of this study can be used as a study in the field of curriculum development science, particularly in the development of the State defense Education curriculum.